Applications of Monte Carlo Methods in Biology, Medicine and Other Fields of Science - Mode, Charles J. (InTechOpen, 2011)
This volume is an eclectic mix of applications of Monte Carlo methods in many fields of research should not be surprising, because of the ubiquitous use of these methods in many fields of human endeavor. In an attempt to focus attention on a manageable set of applications, the main thrust of this book is to emphasize applications of Monte Carlo simulation methods in biology and medicine.